What are the drivers of shadow economy? A further evidence of economic integration and institutional quality. Issue 1 (2nd January 2021) - Canh, Phuc Nguyen; Schinckus, Christophe; Dinh Thanh, Su
Abstract : This article uses panel-corrected standard errors (PCSE) estimator and dynamic fixed effects autoregressive distributed lag (DFE ARDL) estimator to examine the influence of the institutional quality and economic integration on shadow economy for a global sample of 112 economies (between 2005 and 2015). Our empirical research shows that the inward foreign direct investment (FDI), trade openness, institutional quality, and shadow economy have bi-causal relationships. Notably, the results show a strong negative impact of institutional quality and FDI inflows but a weaker negative influence of trade openness on shadow economy. There is also long-run cointegration between institutional quality, economic integration with shadow economy, and heteroscedastic effects of these factors in short run- and long run. Especially, trade openness has a negative impact in both short run and long run, while FDI inflows have a negative influence in the short run but it is positive in the long run. Interestingly, the influence of the institutional quality is quite heterogeneous since the control of corruption and the rule of law have a significant negative impact in the short run, while the political stability has significant negative impact in the long run.